Brisk Walking Education in Hypertension Control in the Working Area of the Kanjilo Health Center - Nur Andani; Rasdiyanah; Eny Sutriya; Aidah Fitriani (LPPM Politeknik Sandi Karsa, 2026)
Hypertension remains a major public health problem with increasing prevalence and significant risk of cardiovascular complications, particularly in primary healthcare settings. Limited community knowledge and low levels of structured physical activity contribute to inadequate non-pharmacological hypertension control. This community service program aimed to improve knowledge, attitudes, and practical skills in hypertension management through structured health education and brisk walking exercise in the working area of Kanjilo Public Health Center. The intervention employed an educational and participatory approach involving 30 adults and older adults with or at risk of hypertension. Activities included baseline assessment, delivery of hypertension education, demonstration and supervised brisk walking practice, and post-intervention evaluation. Results showed substantial improvements in cognitive and behavioral outcomes. The proportion of participants with good knowledge increased from 40.0% to 86.7%, positive attitudes from 46.7% to 83.3%, and understanding of physical activity benefits from 43.3% to 90.0%. Additionally, 83.3% were able to correctly perform brisk walking, and 86.7% expressed commitment to regular physical activity. These findings indicate that integrating health education with moderate-intensity aerobic exercise is feasible and effective in strengthening community-based hypertension control. The program demonstrates potential as a promotive and preventive model within primary healthcare services.